Model Peningkatan Kinerja Pemasaran pada Ikatan Wanita Pengusaha Indonesia (IWAPI) Kabupaten Kudus: Analisis Kemampuan Inovasi sebagai Variabel Mediasi - Marka, Mira Meilia; Rahayu, Tina; Septanti, Annisya Lutfi; Nijwah, Izzah Sarirotun (Innovative: Journal Of Social Science Research, 2024)
This study aims to analyze the impact of social capital and human capital on marketing performance, with innovation capability as a mediating variable. The research object comprises all members of IWAPI (Indonesian Women Entrepreneurs Association) in Kudus Regency, totaling 40 womenpreneurs. The findings reveal that social capital significantly influences innovation capability but does not directly affect marketing performance. On the other hand, human capital has a positive and significant impact on marketing performance, both directly and through partial mediation by innovation capability. These results indicate that developing innovation capability is crucial for improving marketing performance. This study enhances understanding of how social and human capital contribute to marketing performance among womenpreneurs in Kudus Regency.